[OP.7A.10] COMMON AND EMERGENT FACTORS ASSOCIATED WITH HYPERTENSION CONTROL IN ROMANIA. (September 2016) - Darabont, R.; Tautu, O.; Ardeleanu, M.; Dorobantu, M.
Abstract : Objective: Romania is an East European country with high mortality rates for ischemic heart and cerebrovascular diseases largely attributable to an increased level of uncontrolled hypertension. We aimed to analyze the data of SEPHAR II epidemiological study (Study for the Evaluation of Prevalence of Hypertension and Cardiovascular Risk in Romania) in order to identify common and emergent factors associated with treatment control in Romanian hypertensives. Design and method: A total of 1975 subjects, selected on the base of stratified proportional sampling and consented to participate in the study, were evaluated during the two study visits. Hypertension was diagnosed according to current ESH-ESC guidelines (>/ = 140/80 mmHg). High blood pressure (BP) variability was defined as visit-to-visit standard deviation (s.d.) of systolic blood pressure (SBP) situated in the 4th percentile with values >/ = 8.49 mmHg. Pulse wave velocity in the aorta (PWVao) was recorded with an oscillometric device (Medexpert Arteriograph IrDA). Results: Uncontrolled blood pressure was positively correlated with rural area of residence, a lower level of education or income, increased PWVao, high BP variability and self-estimation of BP values as being high, whereas was inversely correlated with antihypertensive treatment based on >/ = 3 drugs, including a diuretic. According to the multivariate analysis for the validation of parameters associated with lack of BP control were found significant: a low level of education {OR = 2.86; 95% confidence interval (CI) 1.84–4.45, p < 0.0001} or income {OR = 1.04; 95% CI 1.03–1.05, p < 0.0001}, increased PWVao {OR = 1.32; 95% CI 1.23–1.43, p < 0.0001}, high BP variability {OR = 0.15; 95% CI 0.07–0.33, p < 0.0001} and treatment with less than 3 antihypertensive or with >/ = 3 drugs, not including a diuretic {OR = 1.91; 95% CI 0.95–3.84, p < 0.031}. A model based on those parameters had a 76% power of prediction for uncontrolled hypertension. Conclusions: The results of this analysis are confirming the association of uncontrolled hypertension with a low level of education or income, are highlighting the efficiency of >/ = 3 drug associations including a diuretic and are bringing up the attention on the potential impact of arterial stiffness and SBP variability on treatment control in hypertensive patients.